EPR study of the peculiarities of incorporating transition metal ions into the diamond structure - Nadolinny, V; Baker, M; Yuryeva, O; Newton, M; Twitchen, D; Palyanov, Y (2005)
In this paper previously obtained data is reviewed and new data is discussed about nickel-containing centers in diamonds. These data are used to suggest interpretation of new data about cobalt-containing centers and to understand the influence of iron on the defects in diamonds grown in the iron system. A newly discovered nickel-nitrogen center has three nitrogen atoms in the first neighbor sphere around the double semi-vacancy and looks like the N3 (P2) center. In diamonds grown in the cobalt system two new types of cobalt-containing centers were found (NLO2 and NWO1). Both centers have electron spin S = 1/2 and hyperfine structure from one cobalt ion (I = 7/2 with natural abundance 100%). A case can be made for a double semi-vacancy structure for these defects. Special growth of diamond in the system enriched in N-15 decreased the line width down to 0.6 G, but gave no direct evidence of the existence of nitrogen in the defect structure. Asymmetrical shapes of the lines in the electron paramagnetic resonance (EPR) spectra of cobalt-containing centers with opposite signs in low and high magnetic field parts of spectra are due to very sensitive spin-Hamiltonian parameters of these defects to the lattice distortions. Annealing of cobalt-containing crystals at 2600 K produces the disappearance of all cobalt-containing EPR spectra, probably due to the capture of an additional nitrogen atom and the creation of a 3d(6) diamagnetic state. In diamonds grown in the iron system with a high content of nitrogen there is evidence of an influence of ferromagnetic inclusion on the exchange interaction between substitutional nitrogen as an additional channel of indirect exchange interaction.